Liquid metal dual-network hydrogel patch with intelligent adhesion
The liquid metal double network hydrogel patch addresses the challenges of rigid biosensors by offering intelligent adhesion and high conductivity, ensuring stable signal transmission and long-term monitoring of physiological signals.
Patent Information
- Application Number
- CN202411352785.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
Existing wearable biosensors face challenges with rigid structures causing discomfort, skin damage, and poor adhesion leading to decreased signal quality, especially for weak EEG signals, due to insufficient adhesion and irreversible bonding of hydrogel materials.
A liquid metal double network hydrogel patch with intelligent adhesion, using gelatin for reversible adhesion, liquid metal for conductivity, and acrylamide and acrylic acid for mechanical strength, combined with temperature-dependent phase change characteristics for on-demand adhesion.
The hydrogel patch provides stable, conformal adhesion, high signal-to-noise ratio, and long-term signal collection, maintaining high fidelity and flexibility, suitable for continuous physiological signal monitoring.
Smart Images

Figure CN119214662A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a liquid metal double network hydrogel patch with intelligent adhesion and a preparation method and application thereof, belonging to the field of bioelectric sensing materials. Background Art
[0002] In recent years, the rapid development of the Internet of Things and artificial intelligence technologies has significantly promoted the widespread application of low-cost, efficient and convenient wearable sensors in the fields of health monitoring and smart medical care. In particular, biosensors based on physiological electrical signal acquisition have become the focus of research because they can directly reflect the health status of the human body and the development trend of diseases. Such sensors have the ability to monitor physiological parameters such as human electroencephalogram (EEG), electrocardiogram (ECG), electromyography (EMG) in real time and continuously, bringing innovative solutions to the biomedical field. At present, traditional signal acquisition methods mainly rely on metal electrodes on the surface of the skin, and conductive glue is required to ensure the effective transmission of electrical signals. However, most wearable sensors on the market currently use rigid structures due to the limitations of material properties, which may cause discomfort to users and may even cause skin damage and other problems. In practical applications, these sensors face many challenges such as comfort, breathability and biocompatibility, which not only affects the user experience, but also may have an adverse effect on signal quality.
[0003] Hydrogel materials have attracted much attention due to their excellent stretchability, biocompatibility and softness. They are particularly suitable for constructing seamless and conformal skin electrode interfaces to achieve accurate detection of various physiological and biochemical information of the human body, including but not limited to body movement, pulse fluctuations, temperature changes, eye movement trajectories, and transcutaneous oxygen pressure monitoring. To achieve the above functions, hydrogel materials usually need to have the following key characteristics: high conductivity and low impedance to ensure that weak EEG signals can be accurately transmitted with a high signal-to-noise ratio (SNR); reliable adhesion to ensure close fit with the skin; excellent flexibility that matches the mechanical properties of the substrate to adapt to various motion states; reusable re-adhesion ability in wearable devices to extend service life; and excellent durability and biocompatibility to ensure the stability of electrode function and long-term safety of biological applications.
[0004] However, in practical applications, the adhesion of most hydrogels is often insufficient. After repeated peeling tests, their adhesion ability is significantly weakened, which leads to a significant decrease in signal quality, especially weak EEG signals at the microvolt level. The fragility, brittleness and irreversible bonding properties of hydrogels are the core factors that cause this limitation, because once the adhesion is lost, it cannot be reactivated.
[0005] Therefore, developing a conformal bioadhesive hydrogel electronic device that simultaneously possesses significant self-adhesion, low interfacial impedance, and excellent sensing performance to meet the needs of high-fidelity epidermal electrophysiological signal monitoring and can reversibly and rapidly re-adhere to the skin after medical diagnostic sensing remains a major challenge that needs to be addressed. Summary of the invention
[0006] The technical solution of the present invention is: in view of the shortcomings of the prior art, a liquid metal double network hydrogel patch with intelligent adhesion and its preparation method and application are proposed. The electrode patch exhibits excellent flexibility, high signal-to-noise ratio, long working life, low impedance and reversible adhesion. The method is simple, efficient and highly repeatable, and effectively overcomes the problem of unstable contact impedance of traditional electrodes. In addition, the hydrogel exhibits good adhesion to the surfaces of various materials and excellent repeated adhesion ability. Based on the temperature-dependent phase change characteristics of the gelatin component, the hydrogel is endowed with adjustable adhesion properties and an intelligent adhesion function that can be separated on demand, which is very suitable for continuous monitoring of physiological electrical signals.
[0007] To achieve the above objectives, the technical solution of the present invention is:
[0008] A liquid metal double network hydrogel patch with intelligent adhesion is a hydrogel patch, the raw materials of which include liquid metal, water, gelatin, acrylamide and acrylic acid. Gelatin, as a thermosensitive polymer, gives the hydrogel reversible adhesion properties, the liquid metal is used to provide cross-linking sites and reduce material impedance, enhance conductivity and provide conductive properties, and acrylamide and acrylic acid provide a strong covalent cross-linking network for the hydrogel, thereby enhancing the mechanical strength of the hydrogel.
[0009] Taking the total mass of the raw materials as 100%, the mass percentage of each component is:
[0010]
[0011]
[0012] A method for preparing a liquid metal double network hydrogel patch with intelligent adhesion comprises the following steps:
[0013] Step 1, adding gelatin to deionized water, stirring at high temperature, and after fully dissolving, adding liquid metal and performing ultrasonic dispersion to obtain a gelatin:liquid metal solution (solution A);
[0014] Step 2: Add acrylamide and acrylic acid into ionized water and stir to fully dissolve them. Then, add initiator ammonium persulfate and stir at a constant temperature to fully dissolve them. Acrylamide: acrylic acid solution (Solution B) is obtained.
[0015] Step 3, adding solution A obtained in step 1 to solution B in step 2, stirring rapidly until the color is uniform to obtain a prepolymer solution, pouring the prepolymer solution into an electrode mold and placing it in an oven for heating, and obtaining a liquid metal double network hydrogel patch with intelligent adhesion after cross-linking.
[0016] In the step 1, the mixing time is 2-3 hours, the temperature is 70° C.-90° C.; the power during ultrasonic dispersion is 200-400 W, and the ultrasonic dispersion time is 10-20 minutes; the liquid metal is at least one of gallium, mercury, gallium-indium alloy, gallium-indium-tin alloy, bismuth-tin alloy, and bismuth-tin-lead-indium alloy; the liquid metal is gallium-indium alloy, and the gallium mass fraction in the gallium-indium alloy is 75.5%, and the indium mass fraction is 24.5%;
[0017] The mixing time in step 2 is 2-3 hours and the temperature is 25°C.
[0018] In step 3, the rapid stirring time is 1-2 minutes, the oven heating temperature is 70° C.-90° C., and the heating time is 10-30 minutes.
[0019] An application of a liquid metal double network hydrogel patch with intelligent adhesion, the prepared liquid metal double network hydrogel patch is attached to the prefrontal region of the brain as a physiological electrical signal sensor, which is used to measure the multi-site EEG signals in the prefrontal region of the brain. At the same time, due to the high temperature of the forehead, the gelatin component in the hydrogel is locally melted, thereby ensuring that the hydrogel and the skin interface are seamlessly adhered in situ, and ice cubes can be used to cool it down after the collection is completed to make it lose its stickiness. This design enables the patch to support multiple long-term, stable adhesion and high-precision signal collection work.
[0020] A flexible wearable three-lead electrode patch is applied to attach a liquid metal double-network hydrogel patch with intelligent adhesion to human skin (physiological electrical signal collection site) for application in clinical medical diagnosis and treatment and wearable bioelectric detection.
[0021] In addition, the liquid metal dual network hydrogel patch serves as an ideal device / skin interface, which can reliably collect high-quality electrophysiological signals even under vibration, sweating and long-term monitoring conditions. A domain adaptive neural network based on transfer learning technology is introduced to mitigate the impact of domain shift and achieve extremely high classification accuracy for EEG-based attention assessment and classification (91.38%).
[0022] Due to the adoption of the above technical solution, the beneficial effects achieved by the present invention are:
[0023] (1) The present invention adopts a strategy of combining gelatin with ultrasonic technology to achieve uniform dispersion of liquid metal gallium-indium alloy droplets in gelatin solution. The large number of hydrogen-bonded groups on the gelatin polymer chain reduces the reaggregation of the dispersed liquid metal gallium-indium alloy droplets, thereby significantly enhancing the conductivity of the gel patch.
[0024] (2) The present invention forms a smart adhesive hydrogel by introducing a thermosensitive material, gelatin. In the hydrogel system, carboxyl (-COOH), hydroxyl (-OH) and amino (-NH 2 ) form a large number of hydrogen bonds, giving the hydrogel excellent adhesion properties, thus ensuring that it can stably and firmly adhere to the skin surface. Thanks to the unique temperature sensitivity of gelatin, the prepared hydrogel can be easily peeled off from the human skin under the cooling effect of an ice pack without causing any damage or residue, and the adhesion strength is stable and can be used multiple times.
[0025] (3) The present invention utilizes acrylamide and acrylic acid to form a covalent cross-linked network, thereby enhancing the thermodynamic stability of the hydrogel, ensuring that when the hydrogel is further melted by the gelatin component under the influence of forehead temperature, the stability of the material structure is guaranteed, thereby achieving stable conformal adhesion properties.
[0026] In addition, the liquid metal double network hydrogel patch prepared by the preparation method of the present invention uses non-hazardous chemicals as the materials, ensuring excellent biocompatibility. In addition, the preparation method of the liquid metal double network hydrogel patch of the present invention requires polymer materials gelatin and acrylamide in the raw materials, which are cheap and easy to obtain, and the materials are green and environmentally friendly, which is conducive to industrial promotion.
[0027] (4) The present invention relates to a liquid metal double network hydrogel patch with intelligent adhesion, and its preparation method and application, which belongs to the field of bioelectric sensing materials. The present invention uses liquid metal, gelatin, acrylamide and acrylic acid as main raw materials. Among them, the liquid metal gallium indium alloy provides key cross-linking sites for the hydrogel, and gives it excellent conductivity and extremely low skin interface impedance. The temperature sensitivity of gelatin enables the hydrogel to have intelligent adhesion ability and can be removed on demand without pain or stimulation. Not only can it be used for synchronous monitoring of physiological signals during exercise, the electrode also exhibits a high signal-to-noise ratio and high signal accuracy, and can be used to evaluate the subject's concentration. At the same time, the hydrogel prepared by the present invention has good mechanical strength, high cost-effectiveness, simple operation, and is suitable for large-scale production and wide promotion. It is expected that the hydrogel will show significant application potential and value in the fields of wound dressings and postoperative care.
[0028] (5) This article discloses a preparation method and application of a liquid metal double network hydrogel patch with intelligent adhesion. The raw materials for its preparation are liquid metal, type A gelatin, acrylamide and acrylic acid monomers, which undergo polymerization reaction under the action of an initiator and cross-link under the action of liquid metal to form a double network hydrogel (wherein the polyacrylamide and polyacrylic acid polymer networks are covalent cross-linked networks, and the gelatin polymer network is a thermosensitive reversible network); the present invention utilizes the temperature-dependent phase change characteristics of the polymer chain in the hydrogel to give the hydrogel the advantages of intelligent adhesion and on-demand removal without pain or stimulation. At the same time, the hydrogel of the present invention has good mechanical strength, low cost, easy operation, and is suitable for large-scale production and promotion and application. It will have a wide range of application value in the fields of wound dressings and postoperative care. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a schematic diagram of the process of preparing the liquid metal double network hydrogel patch with intelligent adhesion of the present invention;
[0030] Figure 2 This is a photo of a liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention, wherein Figure 2 a is a photo of the hydrogel. Figure 2 b is a real photo of the flexible gel electrode patch loaded with PGEH-0.6 hydrogel;
[0031] Figure 3 This is an electron microscope microscopic structure photo of a liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention. Figure 3 a is the electron microscope photo of PGEH, Figure 3 b is an electron microscope photo of PGEH-0.6;
[0032] Figure 4 This is a rheological curve test diagram of the liquid metal double network hydrogel and PEH hydrogel with intelligent adhesion prepared by the preparation method of the present invention. Figure 4 a is the PGEH-0.6 test image, Figure 4 b is the PEH test diagram;
[0033] Figure 5 These are optical images of the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention on different substrates, (a) zinc sheet, (b) copper foil, (c) glass, (d) plastic, (e) 100g weight, (f) skin and (g) optical images of microscopic adhesion of skin;
[0034] Figure 6 a and Figure 6b are impedance spectrum comparison diagrams of the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention and a commercial electrode, as well as impedance curves at 10, 100 and 1000 Hz;
[0035] Figure 7 a is an electrocardiogram curve collected by the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention, Figure 7 b is the comparison curve of the stability of the hydrogel patch and the commercial electrode in collecting ECG signals;
[0036] Figure 8 a is a schematic diagram of the collection of a liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention; Figure 8 b is an electromyographic curve collected by the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention, and a stability comparison curve with commercial electrodes;
[0037] Fig. 9 This is a 48-hour electroencephalogram curve collected by the liquid metal double-network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention, and the inset is its corresponding power spectrum density diagram.
[0038] Fig.10 a is the electroencephalogram curve of the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention and the commercial electrode after collecting for 6 hours, Fig.10 b is the corresponding power spectrum density plot.
[0039] Fig.11 a is a schematic diagram of the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention for EEGNet machine learning, Fig.11 b is the accuracy and loss curve, Fig.11 c is the corresponding confusion matrix diagram.
[0040] Fig.12 It is a schematic diagram of the liquid metal double network hydrogel patch with intelligent adhesion prepared by the preparation method of the present invention being used in a personalized attention evaluation system. DETAILED DESCRIPTION
[0041] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0042] like Figure 1 As shown, a method for preparing a liquid metal double network hydrogel patch with intelligent adhesion comprises the following steps:
[0043] Step 1, mixing gelatin, liquid metal and deionized water in a mixed solution, stirring at high temperature, adding liquid metal after fully dissolving and performing ultrasonic dispersion to obtain a gelatin:liquid metal solution (solution A);
[0044] Step 2, mixing acrylamide, acrylic acid and deionized water, and after fully dissolving, adding initiator ammonium persulfate and stirring at a constant temperature to fully dissolve it, to obtain an acrylamide:acrylic acid solution (solution B);
[0045] Step 3, adding solution A obtained in step 1 to solution B in step 2, stirring rapidly until the color is uniform to obtain a prepolymer solution, pouring the prepolymer solution into an electrode mold and placing it in an oven for heating, and obtaining a liquid metal double network hydrogel patch with intelligent adhesion after cross-linking.
[0046] Example 1
[0047] A method for preparing a liquid metal double network hydrogel patch with intelligent adhesion, specifically comprising the following steps:
[0048] Step 1: Weigh 3g of type A gelatin and 0.6g of liquid metal gallium-indium alloy and add them into 5ml of deionized water. Stir at 90°C for 3h to fully dissolve the gelatin. Then, use a cell disruptor with an ultrasonic power of 300w to ultrasonicate for 25min in an ice bath to obtain a gelatin: liquid metal solution; the mass fraction of gallium in the gallium-indium alloy is 75.5%, and the mass fraction of indium is 24.5%;
[0049] Step 2: Weigh 5 g acrylamide, 0.5 g acrylic acid and 30 mg ammonium persulfate initiator, add them into 5 ml deionized water, and stir at room temperature for 3 h to fully dissolve them to obtain an acrylamide:acrylic acid solution;
[0050] Step 3: Add the solution obtained in step 1 to the solution in step 2, stir quickly with a glass rod for 2 minutes until the color is uniform to obtain a hydrogel prepolymer solution, pour it into an electrode mold and place it in an oven at 90°C and heat it for 20 minutes to obtain a liquid metal double network hydrogel patch with smart adhesion, which is named PGEH-0.6.
[0051] Example 2
[0052] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0.2 g, and the obtained product is named PGEH-0.2 electrode patch.
[0053] Example 3
[0054] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0.4 g, and the obtained product is named PGEH-0.4 electrode patch.
[0055] Example 4
[0056] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0.8 g, and the obtained product is named PGEH-0.8 electrode patch.
[0057] Comparative Example 1
[0058] The difference from Example 1 is that the mass of the liquid metal gallium-indium alloy added in step 1 is 0 g, and the obtained product is named PGEH-0 electrode patch.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that the mass of gelatin added in step 1 is 0 g, and the obtained product is named PEH electrode patch.
[0061] Figure 2 This is a photo of a patch of PGEH-0.6 gel electrode in Example 1 loaded on a printed circuit. Figure 2 It can be seen that the diameter of the PGEH-0.6 gel electrode is 0.9 cm, the thickness is 2 mm, and the size of the printed circuit is 2.5*12 cm 2 , has good bending properties, meeting the needs of wearable flexible electronic devices.
[0062] Figure 3 a is a scanning electron microscope (SEM) image of the PGEH-0 electrode patch obtained in Example 2 of the present invention, Figure 3 b shows a scanning electron microscope (SEM) image of the PGEH-0.6 electrode patch obtained in Example 1 of the present invention. As can be seen from the figure, the hydrogels are all porous structures, and in the voids of the PGEH-0.6 structure, the liquid metal is evenly dispersed in the double network hydrogel.
[0063] like Figure 4As shown in a, the prepared liquid metal double network gel PGEH-0.6 was subjected to rheological tests. In the test, the sample was evenly spread on the plate of the rheometer (MCR 702e MultiDrive), and after it was left to stand for 2 minutes to reach thermal equilibrium, the rheological experiment was carried out. The starting temperature of the scan was 25°C, and the temperature was increased to 55°C at a heating rate of 5°C / min. During the experiment, a 40mm diameter aluminum flat plate fixture was used, the gap was set to 1mm, the strain range was controlled at 1% (to ensure that it was within the linear viscoelastic region), and the angular frequency was set to 10rad / s. To ensure data accuracy, three parallel experiments were performed on each sample. The dynamic temperature scanning curve shows that when the temperature exceeds 30°C, the storage modulus (G') of the PGEH hydrogel is significantly reduced by 81.37%, thus proving its thermosensitivity in the temperature range of 30°C-40°C. On the contrary, as Figure 4 As shown in (b), both the storage modulus (G') and loss modulus (G") of the PEH hydrogel showed an increasing trend without obvious temperature-dependent response. In addition, the storage modulus of PGEH always exceeded the loss modulus throughout the temperature scan. Therefore, despite the local melting of the gelatin molecules, the hydrogel still maintains solid-like elasticity when the temperature is kept below 50°C. When the PGEH hydrogel comes into contact with warm skin, the body temperature triggers the melting of the gelatin molecules, while the acrylamide cross-linked network ensures its shape stability and tight adhesion. Figure 5 These are optical images of the adhesion of the liquid metal double network hydrogel prepared in Example 1 of the present invention to different substrates. It can be seen that the PGEH-0.6 hydrogel can achieve good interfacial adhesion with the organic / inorganic interface and can produce stable contact with the skin, which is beneficial to form conformal contact with the adherend during the application process and give full play to the performance advantages of the bioelectric sensing material.
[0064] The electrical properties of the liquid metal double network hydrogel patch were measured using the Shanghai Chenhua Co., Ltd. CHI760E electrochemical workstation. The electrode patch was cut into 10mm×10mm size, and the working electrode (WE), reference electrode (RE) and counter electrode (CE) were placed at the same position on the skin for testing the skin interface impedance test. The impedance spectra of PGEH electrodes with different LM contents and commercial Ag / AgCl gel electrodes (Danish AMBU N-00-S / 25 gel electrodes) are shown in Figure 2. Figure 6 As shown in a, liquid metal helps to reduce the interfacial impedance of hydrogel and 5 The impedance value within Hz frequency is still better than that of commercial electrodes ( Figure 6 b), also demonstrated that the liquid metal double network hydrogel patch has excellent conductivity.
[0065] The obtained ECG signals were used to monitor the subtle ECG signals and were placed on the left chest, right chest and left abdomen respectively to obtain Figure 7 The ECG signal of the subject shown in a shows that the tested ECG data has a good peak morphology, and the PQRST characteristic peaks can be clearly seen. These signals play an important role in diagnosing myocardial ischemia, myocardial infarction and various arrhythmias, such as Figure 7 As shown in b, the signal of PGEH-0.6 is still stable after 24 hours of use, which is comparable to that of commercial electrodes. Figure 8 As shown in a, place three hydrogel electrode patches as shown in the schematic diagram. Figure 8 b It can be seen that the dual-network hydrogel patch can clearly capture surface electromyographic signals and exhibit stable and lasting performance, comparable to commercial electrodes. This fully demonstrates that the neural electrode has excellent stretchability, reliability and stability, and will not affect the accurate measurement of surface electromyographic signals due to resistance changes caused by arm muscle movement. This feature further proves the feasibility of the neural electrode in clinical applications.
[0066] Compared to ECG and EMG signals, accurately capturing EEG signals remains a formidable challenge due to their inherently weak signal potentials, measured in microvolts (μV), and their sensitivity to scalp interference. Due to the conformal contact of PGEH electrodes and their special adaptation to the hairy scalp, e.g. Fig. 9 As shown in Figure 2, the recorded EEG signals exhibited long-term and high-fidelity alpha waves (10 Hz) during the signal acquisition period, which could be maintained for up to 48 hours. Fig.10 As shown in a, the commercial electrode showed significant activity decay after 6 hours of continuous use. Fig.10 It is difficult to observe clear alpha waves in b, which further highlights the great potential of dual-network hydrogels in the precise monitoring of human electrophysiological signals.
[0067] Based on the accurate EEG characteristic signals collected by dual network hydrogel, such as Fig.11 As shown in a, the attention assessment test and EEGnet machine learning algorithm can be used to classify and evaluate the concentration levels of different subjects. Fig.11 As shown in b, after 200 trainings, the training loss steadily decreased to 0.021. Fig.11 c showed excellent recognition accuracy (91.38%). Referring to previous studies on the correlation between EEG activity and attention, we found that the stable EEG signal patterns under different attention states showed significant consistency in repeated acquisitions. Fig.12 The schematic diagram shows that based on the attention assessment system, personalized feedback can be provided to students or employees in different concentration situations in a timely and effective manner, thereby improving their work efficiency.
[0068] In summary, the present invention has developed a liquid metal double network hydrogel patch with intelligent adhesion. The flexible patch has good thermoreversible adhesion performance, can be used multiple times without loss of adhesion, and provides long-term stability for bioelectric signal acquisition. The liquid metal double network hydrogel patch prepared by the preparation method of the present invention has high conductivity and good bioadaptability. It has good signal acquisition performance and can collect tiny epidermal electrophysiological signals (including electrocardiogram, electromyogram and electroencephalogram). It can not only be used as a portable sustained attention assessment device in scientific research and daily life, but also supports multifunctional diagnosis and health assessment in medical applications.
[0069] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art who is familiar with the present invention may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A liquid metal double network hydrogel patch with intelligent adhesion, characterized in that: The raw materials of the liquid metal double network hydrogel patch include liquid metal, water, gelatin, acrylamide and acrylic acid, and also include ammonium persulfate; Taking the total mass of the raw materials of the liquid metal double network hydrogel patch as 100%, the mass percentage of each component is:
2. The liquid metal double network hydrogel patch with intelligent adhesion according to claim 1, characterized in that: The liquid metal is at least one of gallium, mercury, gallium-indium alloy, gallium-indium-tin alloy, bismuth-tin alloy, and bismuth-tin-lead-indium alloy.
3. The liquid metal double network hydrogel patch with intelligent adhesion according to claim 2, characterized in that: The mass fraction of gallium in the gallium-indium alloy is 75.5%, and the mass fraction of indium is 24.5%.
4. A method for preparing a liquid metal double network hydrogel patch with intelligent adhesion, characterized in that The steps of the method include: Step 1, mixing gelatin, liquid metal and water to obtain solution A; Step 2, mixing acrylamide, acrylic acid and water, and after fully dissolving, adding ammonium persulfate and stirring at a constant temperature to obtain solution B; Step 3, adding solution A obtained in step 1 to solution B obtained in step 2, stirring to obtain a prepolymer solution, pouring the prepolymer solution into an electrode mold and placing it in an oven for heating to obtain a liquid metal double network hydrogel patch with intelligent adhesion.
5. The method for preparing a liquid metal double network hydrogel patch with intelligent adhesion according to claim 4, characterized in that: In the step 1, the mixing time is 2-3 hours and the mixing temperature is 70° C.-90° C.
6. The method for preparing a liquid metal double network hydrogel patch with intelligent adhesion according to claim 4, characterized in that: In step 2, the mixing time is 2-3 hours and the mixing temperature is 25°C.
7. The method for preparing a liquid metal double network hydrogel patch with intelligent adhesion according to claim 4, characterized in that: In step 3, the stirring time is 1-2 minutes, the oven heating temperature is 70° C.-90° C., and the heating time is 10-30 minutes.
8. Application of a liquid metal double network hydrogel patch with intelligent adhesion, characterized in that: The prepared liquid metal double network hydrogel patch is attached to the prefrontal region of the brain as a physiological electrical signal sensor to measure multi-site EEG signals in the prefrontal region of the brain.
Citation Information
Patent Citations
Ti<3>C<2>T<x> composite double-network hydrogel and preparation and application thereof
CN110760075A
High-elasticity hydrogel sensor and preparation method thereof
CN114149595A
Hydroximic acid grafted gelatin / polyacrylamide double-network hydrogel adsorbent as well as preparation method and application thereof
CN117753388A
Flexible hydrogel electrode for high-density physiological signal detection and preparation method thereof
CN117796816A
Functionalized implantable flexible electrode and application thereof
WO2020107345A1
Cited By
Medical data processing method and system for reversible adhesion of hydrogel brain electrode
CN121237449A
Medical data processing method and system for reversible adhesion of hydrogel brain electrodes
CN121237449B
Liquid metal-gelatin-based thermoresponsive conductive composite hydrogel for 3D printing and preparation method and application thereof
CN122941025A
